Reducing Householders' Grocery Carbon Emissions: Carbon Literacy and Carbon Label Preferences. Issue 4 (November 2013) - Sharp, Anne; Wheeler, Meagan
Government and industry are increasingly calling upon households to lower their carbon emissions through improved consumption choices. Grocery products, because of their high volume, are a significant contributor to emissions and have become a focus for behaviour change efforts. Yet the assumption that the consumer knows, cares and can comprehend the information they are given in a carbon label is yet to be empirically established as consumer carbon literacy and perceptions of carbon label designs are not yet well researched. This paper finds that Australian householders have low pre-existing carbon knowledge and are consequently poor at identifying high carbon emitting grocery products, unaided. This suggests a role for on-pack carbon labels to assist at-shelf choices. However, given the quick and habitual nature of grocery shopping, a significant challenge lies in how best to communicate emissions for consumer cut-through and awareness. Testing of competing carbon labels finds that householders give highest preference ratings to formats that show emissions relative to other products, rather than stand alone, and for ones that use the traditional traffic light colour system. Governments, manufacturers, and marketers can use these findings in their efforts to raise consumers' carbon literacy and encourage more informed grocery carbon emission choices.